Unraveling the Strategies Used by the Underexploited Amaranth Species to Confront Salt Stress: Similarities and Differences With Quinoa Species - Estrada, Yanira; Fernández-Ojeda, Amanda; Morales, Belén; Egea-Fernández, José M.; Flores, Francisco B.; Bolarín, María C.; Egea, Isabel (Frontiers in Plant Science, 2021)
Yield losses due to cultivation in saline soils is a common problem all over the world as most crop plants are glycophytes and, hence, susceptible to salt stress. The use of halophytic crops could be an interesting alternative to cope with this issue. The Amaranthaceae family comprises by far the highest proportion of salt-tolerant halophytic species. Amaranth and quinoa belong to this family, and their seeds used as pseudo-cereal grains have received much attention in recent years because of their exceptional nutritional value. While advances in the knowledge of salt tolerance mechanisms of quinoa have been remarkable in recent years, much less attention was received by amaranth, despite evidences pointing to amaranth as a promising species to be grown under salinity. In order to advance in the understanding of strategies used by amaranth to confront salt stress, we studied the comparative responses of amaranth and quinoa to salinity (100 mM NaCl) at the physiological, anatomical, and molecular levels. Amaranth was able to exhibit salt tolerance throughout its life cycle, since grain production was not affected by the saline conditions applied. The high salt tolerance of amaranth is associated with a low basal stomatal conductance due to a low number of stomata (stomatal density) and degree of stomata aperture (in adaxial surface) of leaves, which contributes to avoid leaf water loss under salt stress in a more efficient way than in quinoa. With respect to Na+ homeostasis, amaranth showed a pattern of Na+ distribution throughout the plant similar to glycophytes, with the highest accumulation found in the roots, followed by the stem and the lowest one detected in the leaves. Contrarily, quinoa exhibited a Na+ includer character with the highest accumulation detected in the shoots. Expression levels of main genes involved in Na+ homeostasis (SOS1, HKT1s, and NHX1) showed different patterns between amaranth and quinoa, with a marked higher basal expression in amaranth roots. These results highlight the important differences in the physiological and molecular responses of amaranth and quinoa when confronted with salinity.